Electrocatalysis on copper–palladium alloys for amperometric formaldehyde sensing. Issue 10 (18th January 2017) - Pötzelberger, Isabella; Mardare, Cezarina Cela; Uiberlacker, Lisa Maria; Hild, Sabine; Mardare, Andrei Ionut; Hassel, Achim Walter
Abstract : A co-evaporated Cu–Pd thin film combinatorial library was screened for electrocatalytic oxidation of formaldehyde by scanning droplet cell microscopy. The best activity was found for 7.5 at% Pd and an amperometric sensor was fabricated and tested. Abstract : Co-evaporation of Cu and Pd was used for the deposition of a relatively small gradient concentration thin film combinatorial library with Pd amounts between 4 and 14 atomic percent (at%). Screening for electrocatalytic oxidation of formaldehyde was performed by scanning droplet cell microscopy along the Cu–Pd compositional spread in alkaline solution and a best material performance for this process was identified for 7.5 at% Pd in Cu confirming results from co-sputtering studies. However, the microstructure and crystallographic analysis of Cu–Pd thin film alloys showed a compositionally induced gradual change of properties without any significant discontinuity. This indicates that the Cu–Pd atomic ratio is the main factor defining the electrocatalytic activity of the investigated alloys. This finding is also confirmed for bulk Cu–Pd alloys where the reproducibility of significant formaldehyde oxidation electrocatalytic activity when using Cu-7.5 at% Pd was demonstrated. An amperometric formaldehyde sensor was fabricated and its reproducibility, repeatability and stability were assessed. During successive anodic formaldehyde current oxidation peak observations a standard deviation value of 8% was measured. Multiple efficient successive use of the same sensor (5 to 10 times) were demonstrated and a maximum of 5% decrease in the current density was observed after 21 days of normal environment storage during a shelf-lifetime evaluation of the sensor. Overall, the study reveals inexpensive approaches for fabrication of multiple use formaldehyde sensors via thermal evaporation or bulk alloy casting, as well as the transfer of the main feature ( i.e. maximum current density for formaldehyde oxidation) from a thin film combinatorial library to bulk samples.